PENGARUH TERPAAN PEMBERITAAN RUU KPK DI KOMPAS TV TERHADAP TINGKAT KEPERCAYAAN MAHASISWA KEPADA PEMERINTAH - Diana Kusumardani Saputri, (2020)
The background of this research is based on large-scale demonstrations conducted by students in various cities in Indonesia. Demonstrations that occurred due to student refusal of the issuance of the revision of the KPK law in September 2019. This study aims to prove whether there is an influence and how much influence the exposure of the draft of law KPK on Kompas TV to the level of student confidence in the government. From the results of the study, the Coverage of the draft of law KPK on Kompas TV can indeed have an effect and also a significant effect on the audience, this is based on the results of the correlation test of -401. Then the results of the determination test of this study showed that the exposure of the draft of law KPK on Kompas TV contributed 16.1% to the level of student confidence in the government, and based on the results of the regression test Y = 28,140 + (-0,312 X) it can be concluded that every time a report of the draft of law KPK on Kompas TV appears, the level of student confidence in the government decreases by 0.312, and for the results of the hypothesis test the t count is 4.306 and the t table is 1.66298. Based on these calculations the t count> t table, then it can be determined that Ho is rejected and Ha is accepted. Thus it can be concluded that the Coverage the draft of law KPK on Kompas TV effects the Level of Student Trust in the Government.